2018
DOI: 10.1088/1751-8121/aa95c7
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic population dynamics in spatially extended predator–prey systems

Abstract: Abstract. Spatially extended population dynamics models that incorporate demographic noise serve as case studies for the crucial role of fluctuations and correlations in biological systems. Numerical and analytic tools from non-equilibrium statistical physics capture the stochastic kinetics of these complex interacting manyparticle systems beyond rate equation approximations. Including spatial structure and stochastic noise in models for predator-prey competition invalidates the neutral Lotka-Volterra populati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
123
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(125 citation statements)
references
References 224 publications
(838 reference statements)
2
123
0
Order By: Relevance
“…a Petri dish) three cyclically competing strains of bacteria coexist for a long time, whereas in the well-mixed environment of shaken flasks two species go extinct quickly. Both theoretical (Reichenbach et al, 2007a(Reichenbach et al, ,b, 2008He et al, 2011;Lamouroux et al, 2012;Rulands et al, 2013;Szczesny et al, 2013Szczesny et al, , 2014Szolnoki et al, 2014;Dobramysl et al, 2018) and experimental (Siegert and Weijer, 1995;Igoshin et al, 2004) studies have revealed that spatio-temporal patterns, as for example propagating fronts or spiral waves, often accompany long-lasting coexistence between different species.…”
Section: The Three-species Casementioning
confidence: 99%
“…a Petri dish) three cyclically competing strains of bacteria coexist for a long time, whereas in the well-mixed environment of shaken flasks two species go extinct quickly. Both theoretical (Reichenbach et al, 2007a(Reichenbach et al, ,b, 2008He et al, 2011;Lamouroux et al, 2012;Rulands et al, 2013;Szczesny et al, 2013Szczesny et al, , 2014Szolnoki et al, 2014;Dobramysl et al, 2018) and experimental (Siegert and Weijer, 1995;Igoshin et al, 2004) studies have revealed that spatio-temporal patterns, as for example propagating fronts or spiral waves, often accompany long-lasting coexistence between different species.…”
Section: The Three-species Casementioning
confidence: 99%
“…The language and also numerical and mathematical tools developed for the investigation of chemical kinetics may be directly transferred to spatially extended stochastic population dynamics. 5,35,36 Aside from the logistic population growth with finite carrying capacity (7), another classical and paradigmatic model in ecology concerns the competition and coexistence of prey with their predator species, as first independently constructed by Lotka and Volterra. 1,3 Let B indicate the prey species, who left on their own merely undergo (asexual) reproduction B → B + B with rate σ.…”
Section: Activity Fronts In Predator-prey Coexistence Modelsmentioning
confidence: 99%
“…Simultaneous interactions within multi-species communities and their effects on temporal population variability have received relatively less attention than pairwise interactions, and have sometimes generated conflicting results (Godoy et al 2017, Grilli et al 2017. Models developed in this context have used a generalized Lotka-Volterra framework of first-order differential equations (Kokkoris et al 2002, Dobramysl et al 2018, or stochastic particle systems (Foley 1994) either with static (e.g., Cattin et al 2004) or dynamic parameters (e.g., Cohen et al 1990). In most of them, long-term stability requires specific parameter combinations and/or variable interaction strength (Taylor 1988, Allesina and Tang 2012, Serv an et al 2018).…”
Section: Introductionmentioning
confidence: 99%